Efficient Cu‐catalyzed Synthesis of Benzimidazoles Using Ammonia as Nitrogen Source in Water. Issue 7 (8th June 2020) - Li, Minxin; Tang, Yanling; Gao, Hui; Rao, Gaoxiong; Mao, Zewei
Abstract: In present work, we have developed an efficient strategy for the synthesis of 2‐substituted benzimidazoles via Cu‐catalyzed Ullmann condensation reaction of o ‐halobenzanilides with ammonia in water. This protocol is applicable to a wide variety of 2‐substituted benzimidazoles bearing functional groups tolerance, which features one‐pot, high yields, functional groups tolerable and green solvent. Abstract : Heterocycles : A newly developed Cu‐catalyzed Ullmann condensation reaction of o ‐halobenzanilides with ammonia has been presented, giving 2‐substituted benzimidazoles in high yields.